2021
DOI: 10.1097/prs.0000000000008661
|View full text |Cite
|
Sign up to set email alerts
|

System-Level Determinants of Access to Flap Reconstruction after Abdominoperineal Resection

Abstract: reatment of low-lying anorectal cancer and pelvic malignancies often involves neoadjuvant chemoradiation followed by abdominoperineal resection or pelvic exenteration. The resulting large soft-tissue defect can undergo primary closure or flap reconstruction. Even though the superiority of each method with regard to wound healing complications remains controversial in the literature, most studies demonstrate that attempts at primary closure following abdominoperineal resection are associated with high morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…9,10 Given these benefits of vertical rectus abdominis myocutaneous flap reconstruction, it is surprising that the frequency of this operation remains extremely low at 6.5 percent. 1 The frequency of flap reconstructions in our abdominoperineal resection patient population is 63 percent over the past 2 years, which is roughly 10-fold higher than that reported by Dayani et al Abdominoperineal resection for low-lying rectal and anal cancer in female patients frequently requires a flap skin paddle to reconstruct the vagina. Therefore, one would expect to see more flap reconstructions in women, but that was not the case.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…9,10 Given these benefits of vertical rectus abdominis myocutaneous flap reconstruction, it is surprising that the frequency of this operation remains extremely low at 6.5 percent. 1 The frequency of flap reconstructions in our abdominoperineal resection patient population is 63 percent over the past 2 years, which is roughly 10-fold higher than that reported by Dayani et al Abdominoperineal resection for low-lying rectal and anal cancer in female patients frequently requires a flap skin paddle to reconstruct the vagina. Therefore, one would expect to see more flap reconstructions in women, but that was not the case.…”
mentioning
confidence: 67%
“…1 Their review of the National Inpatient Sample database demonstrated that patient-level factors such as age, history of neoadjuvant chemoradiation therapy, large hospital size, and urban teaching setting increase the likelihood of flap reconstruction. 1 The clinical benefits of vertical rectus abdominis myocutaneous flap reconstruction of abdominoperineal resection defects have been well described. In 2008, Butler et al published a retrospective review comparing flap reconstruction with primary closure of abdominoperineal resection defects.…”
mentioning
confidence: 99%
See 2 more Smart Citations